Influence of Cell Design on Temperatures and Temperature Gradients in Lithium-Ion Cells: An In Operando Study. Issue 6 (5th March 2015) - Waldmann, Thomas; Bisle, Gunther; Hogg, Björn-Ingo; Stumpp, Stefan; Danzer, Michael A.; Kasper, Michael; Axmann, Peter; Wohlfahrt-Mehrens, Margret
Abstract : The study observes thermal behavior of six Lithium-ion batteries with different cell designs. In operando temperature measurements are conducted using a thermographic camera as well as internal and external temperature sensors. The investigated cell designs include pouch cells as well as two high-power and two high-energy 18650 battery types. It is found for all cells that maximum temperatures of the cells correlate linearly with the discharge current. This trend is explained by basic physical laws. High-power and high-energy cells show significant differences, which correlate with electrode thickness and cell resistance. Furthermore, the influence of heat transport at different ambient conditions (climate chambers and use of heat sink) is discussed. A general difference is found for the temperature gradients inside pouch and cylindrical cells.